Konstrukcja macierzy Burta dla obiektów symbolicznych - Dudek, Andrzej (The Construction of Burt Table for Symbolic Objects, 2009)
Burt table is one of the most important tools of multidimensional correspondence analysis. The algorithm of creation for categorical data is well-known and described in literature of subject. In this paper, an extension of methods of correspondence analysis onto data represented in form of symbolic objects is proposed. Basing on fuzzy coding introduced by Greenacre (1984), the method of creation code matrix and Burt table is proposed for symbolic data in form of intervals, list of categories, and list of categories with weights. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 299-306